2022
DOI: 10.3389/fphar.2022.925377
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonist-associated tumor adverse events: A real-world study from 2004 to 2021 based on FAERS

Abstract: Background: GLP-1 receptor agonists (GLP-1RA) have demonstrated cardiovascular benefits, but the relationship between GLP-1RA and tumors is controversial. Recently, clinical trials reported higher rates of malignancy with semaglutide than control group. As real-world evidence of GLP-1RA-associated tumor risk is very limited, we explored the association of GLP-1RA and all types of neoplasms by mining the FDA Adverse Event Reporting System (FAERS) database.Methods: The FAERS data from the first quarter (Q1) of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
0
35
0
3
Order By: Relevance
“…A recent real-world study using FAERS data from the first quarter of 2004 to the second quarter of 2020 reported significant signals between GLP-1RA and certain tumors, including medullary thyroid cancer, papillary thyroid cancer, malignant pancreatic neoplasms, islet cell neoplasms and APUDoma NEC. They suggested the combination of GLP-1 RA and DPP4i might have caused the increased reporting rate in tumors 6 . On the contrary, Ruette et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent real-world study using FAERS data from the first quarter of 2004 to the second quarter of 2020 reported significant signals between GLP-1RA and certain tumors, including medullary thyroid cancer, papillary thyroid cancer, malignant pancreatic neoplasms, islet cell neoplasms and APUDoma NEC. They suggested the combination of GLP-1 RA and DPP4i might have caused the increased reporting rate in tumors 6 . On the contrary, Ruette et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies support therapeutic benefits of GLP-1 RA with regard to cardiovascular outcomes in type 2 diabetes 3 . However, as incretins stimulate cellular proliferation, concerns have been raised regarding a potentially increased risk of thyroid and pancreatic cancer, associated with GLP-1 RA usage 4 6 . Studies have reported increased risk of pancreatic cancer associated with GLP-1 RA usage 7 9 , while other studies did not find such an association 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Insbesondere über ein vermehrtes Auftreten von Schilddrüsen-und Pankreastumoren wurde wiederholt berichtet [44][45][46]. Das allgemeine Tumorrisiko scheint nicht erhöht zu sein, wie Daten aus der FDA Adverse Event Reporting System (FEARS) Datenbank im Zeitraum 2004-2020 nahelegen [47]. Jedoch gilt es zu beachten, dass die meisten Analysen den Einsatz der GLP-1-RA für die Diabetes-Indikation und damit in niedrigerer Dosierung beinhalten und der Nachbeobachtungszeitraum mehreren Monaten bis einige Jahren umfasst.…”
Section: Langzeitrisiken Von Glp-1-raunclassified
“…Dem entgegen steht das generell erhöhte Tumorrisiko bei Adipositas und deren Komorbiditäten, das ebenfalls berücksichtigt werden muss. Ein erhöhtes Risiko für Tumoren der Schilddrüse, insbesondere medulläre und papilläre Schilddrüsenkarzinome wurde wiederholt gezeigt [44,47]. Auch eine aktuelle Studie konnte ein erhöhtes Risiko nach 1 bis 3 Jahren Therapie mit Liraglutid für Schilddrüsenkarzinome aller Art (HR 1,58), insbesondere für medulläre Schilddrüsenkarzinome (HR 1,78), zeigen [45].…”
Section: Langzeitrisiken Von Glp-1-raunclassified
See 1 more Smart Citation